PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, DAN KOMPETENSI KARYAWAN TERHADAP KINERJA DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI - Shinta Haryanti; Muhammad Cholil (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
The purpose of this study serve to determine the effect of leadership style, organizational culture, and employees’ competence on performance with organizational commitment as a mediating variable (case study at the Islamic Hospital in Klaten). This study is a descriptive empirical study with a quantitative approach. The type of data used is primary data and secondary data. The population in this study is the nurse-patient unit Klaten Islamic Hospital number 194 and number 131 samples were taken more than 1 year. Nonprobability sampling technique using sampling with purposive sampling method and then diproporsionalkan. Instrument research using questionnaires. Data analysis includes test instrument, the classical assumption test, and test hypotheses with linear regression as a tool of analysis using SPSS 17. Based on the discussion of the results of this study be concluded that the employees’ competency effect on the employee performance, while the leadership style and organizational culture had no effect improves employee performance. After attending the variables of organizational commitment as a mediating variable that affects only one variable, namely the competence of employees, while others may not affect performance significantly with or without a mediating variable.